Exploring teachers’ technology acceptance during COVID-19 pandemic: A systematic review (2020-2022) - Teo Woon Chun; Melor Md Yunus (International Journal of Evaluation and Research in Education (IJERE), 2023)
The emergence of novel coronavirus disease 2019 (COVID-19) caused teachers shifting from conventional mode to emergency remote teaching with technology use. Nevertheless, review of technology acceptance level of teachers towards technology is limited, despite its significance in sustaining education during the pandemic. This study aimed to explore teachers’ technology acceptance level and factors affecting their intentions of accepting technology in the COVID-19 pandemic. With the adherence of preferred reporting items for systematic review and meta-analyses (PRISMA) 2020 statement and list of inclusion and exclusion criteria, 22 articles which were published from 2020 to present and related to the research focus had been identified from Scopus and Web of Science databases. The findings depicted that most teachers hold high acceptance level towards using technology to deliver lessons during the COVID-19. There were five key factors affecting teachers’ intentions in accepting technology, namely: i) Perceived usefulness; ii) Perceived ease-of-use; iii) Attitude; iv) Social influence; and v) Facilitating conditions. This study has provided insight to stakeholders on teachers’ technology acceptance during the pandemic. Future studies are recommended to conduct systematic reviews on technology acceptance from students’ perspective by identifying published papers from more databases such as ERIC and Google Scholar.